PRODUCTION OF CARBON NANOFIBERS BASED ON COAL TAR AND POLYACRYONITRILE BY ELECTROSPINNING METHOD - B.T. Yermagambet,; M.K. Kazankapova,; A.T. Nauryzbayeva,; Zh.M. Kassenova, (Academic Scientific Journal of Chemistry, 2021)
The article presents experiments on obtaining composite fibers based on Shubarkol coal tar (CT) and polycarlonitrile (PAN) by electrospinning in a laboratory setup. As a result of energy dispersive X-ray spectroscopy and SEM microscopy, the elemental composition (C-85.83%) and the diameter of the carbon fiber were determined, which ranged from 89.0 nm to 449.8 nm. The resulting CNF was subjected to oxidation in air at 300 °C, the holding time was 1 hour, after which the carbonization process was carried out at 800 °C, followed by cooling to room temperature. Raman spectra were recorded to study the degree of graphitization. The results of Raman scattering of light (RS) showed the degree of graphitization - 15.98%. Ratio I (D) / I (G) = 0.99, I (G) / I (D) = 1. The broad bands D (disordered part) and G (ordered graphite structure) suggest that CNFs contain partially graphitized carbon along with amorphous carbon. The ID / IG ratio represents the conversion of disordered carbon to graphite carbon during carbonization. The resistance of this material is 70-200 ohms. The results obtained confirm the semiconductor nature of the conductivity. On the basis of SEM drawings of CNFs from CT and PAN, it was found that the structure of CNFs after oxidation and carbonization retains the original fibrous structure. It was also found that the diameter of nanofibers decreases from 320.5 - 625.7 nm to 89-449.8 nm. Thus, the proposed method of obtaining CNF is built on the basis of the electrospinning method, which is the most promising method of industrial production